Comparative Analysis of Settlement and Pore Water Pressure of Road Embankment on Yan soft soil Treated with PVDs - Rufaizal Che Mamat; Anuar Kasa; Siti Fatin Mohd Razali (Civil Engineering Journal, 2019)
The application of prefabricated vertical drains (PVDs) in the road embankment construction has been successfully performed in many projects throughout the country. The simulation of finite element method (FEM) can assist engineers in modelling very complex structures and foundations. This paper presents a plane–strain numerical analysis that was performed to verify the effectiveness of the model embankment stabilised with PVD using Plaxis 2D version 8. This study employed the smear effect of permeability ratio (kr) of 3 in the PVD modelling. The data of settlement and pore water pressure in the left and right sides of road embankment were monitored for 177 days, then the data were collected and compared by a numerical simulation. The coefficient of determination (R2) was used to assess the performance of the comparative analysis. The results of numerical simulation on settlement and pore water pressure obtained a coefficient of determination of greater than 0.9 which has reached a good agreement with those of the field measurement. On other the hand, there was no significant difference in the performance between both sides of the embankment. The smear effect parameter (kr = 3) is recommended for PVD designs and can provide accurate FEM prediction.